Karma In The Hinduism And Buddhism Perspective - Husnul Khotimah; Muhammad Sandi Rosyadi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
This paper will explain about ideology that often called